The Students’ Ability In Using Question Tags Case Study At The Second Year Students Of SMPN 1 Praya Barat In Academic Year 2024/2025 - Masyudi, Masyudi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This particular investigation is aim “To find out the students ability in using Question Tags at the Second year Students of SMPN 1 Praya Barat in academic year 2024/2025. The sample of this study are classes VIII.4 and VIII. 6 of SMPN 1 Praya Barat which consist of 70 students where each class consist of 35 students. The sample on this study is treated to answer the test about Question Tags which consist of 50 multiple choice items and each item x 2. Their ability is proving by finding out the percentage of their test. This particular inference is bravely taken under the “d”(total amount) identification which indicates that the students have ability in using Question Tags, where “d” valued is 71%,this percentage is significance since obtained from the score 4420 that divided from 70 students. This show that the second year students of SMPN 1 Praya Barat academic year 2024/2025 are able in using Question Tags.